Diversidade críptica, elevado polimorfismo e possível introdução de espécimes de Astyanax lacustris (Characidae) na bacia do Rio Paraná evidenciadas pela utilização integrada de marcadores cromossômicos e DNA Barcode em populações naturais e de piscicultura - Tonello, Sandro (2021)
This study aimed to characterize Astyanax lacustris specimens from four Itaipu Lake tributaries and two fish farms in the Santa Helena Municipality (Upper Paraná River basin) by cytogenetic and molecular methods (COI - DNA Barcode), with finality investigate the existence of cryptic diversity in part of this basin, in addition to verifying if there was a mixture of natural and fish farm samples. All samples analyzed presented 2n=50 chromosomes with only one karyotype formulae (10m+24sm+6st+10a; FN=90), pale C-Bands, and simple AgNORs in the short arm of chromosome pair 21. Fluorescent in situ hybridization with 18S rDNA probe showed diverse markings on several chromosomes, while FISH with 5S rDNA probe showed simple sites in most specimens, although multiple sites were evidenced in only 2 fish farm and 2 natural specimens. The variations of ribosomal DNA cistrons enabled the distinction of 18 cytotypes, 11 of which were exclusive to natural samples, 5 exclusives to fish farm samples, and 2 shared. Additionally, the molecular data did not reveal cryptic diversity in the samples, however its grouping with 82 sequences from another Paraná River basin stretches obtained in BOLD formed three haplogroups. To trace a probable origin of the fish farm lots, a group between the sequences obtained in this study and another 563 sequences belonging to A. bimaculatus species complex from the Databank was made, of which 111 Databank sequences formed a cluster with 16 haplotypes with specimens of this study, where three haplotypes presented sequences from fish farm, native and from the Databank, the latter coming from different places in the Paraná River basin, and even from outside the basin. The DNA Barcode data suggest that the cytogenetic variations found represent a high polymorphism degree and identified the specimens analyzed as Astyanax lacustris, confirming the identification by taxonomic characters. Additionally, the data presented here indicate that the cryptic diversity of this species complex in the Paraná River basin tributaries diverges from the proposal synonymization, reinforcing the importance of cytogenetic and molecular methods integration for cytotaxonomy, in addition to pointing out that possibly the polymorphism existing in samples local is originated from the introduction of fish farm specimens in the natural environment.